Two new species of Gaeolaelaps Evans & Till (Acari: Laelapidae) from the Andes Mountains, Peru - Joharchi, Omid; Friedrich, Stefan (Zootaxa, 2021)
Two new species of mites in the genus Gaeolaelaps (Laelapidae) are described from specimens collected from soil-litter in the Peruvian Andes – G. acanthopedus sp. nov. and G. andensis sp. nov.. Both species are consistent with the current concept of the genus Gaeolaelaps Evans & Till. The genus Gaeolaelaps is reported for the first time from Peru.